«Courageous memory, sad singing skeleton»: The house and the experiences of being in Trilce (1922) by César Vallejo - Carhuaricra Anco, Miguel Ángel (2022)
This article explores the meanings of the house in César Vallejo’s Trilce. The guiding idea of this study is that in poems «XXVII», «XXVIII» and «LXI», poetic images disclose affective senses of the house and connote connection, restitution, and understanding of the self. For this purpose, we first take stock of the image-centered appreciations in Trilce; then we explain the conception of poetic image and house from Gaston Bachelard's phenomenology of imagination, and we delineate the features of the poet's home from Danilo Sánchez Lihón's evocation. Subsequently, we analyze and interpret the poetic images of the mentioned poems; and, finally, we reflect on the transcendence of the poetic image for the understanding of Trilce.